2014
DOI: 10.1021/np500178s
|View full text |Cite
|
Sign up to set email alerts
|

Diterpenes from the Endangered Goldenrod Solidago shortii

Abstract: Species extinction is tantamount to loss of chemical diversity, and so it is important to seize all opportunities to study species on the brink of extinction. Such studies are often hampered by the limited material available, but that obstacle is surmountable through collaboration with botanical gardens and advances in instrumentation. The goldenrod Solidago shortii is one example of an endangered species native to the United States. From S. shortii, one known diterpene (1), two new diterpenes (2 and 3), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The latest generation of high-field NMR spectrometers equipped with microcryoprobes, however, extends the lower limits of detection of protonated species to the picomole scale. , The extreme sensitivity makes these probes ideal tools to study mass-limited samples such as isolated low-abundance proteins, peptides, and small molecules, and difficult to express proteins. For example, this technology has been used to determine the structures of molecules that can only be isolated in minute amounts (micrograms or less) from natural sources such as deep sea sponges, , red algae, and plants . It is also used by structural genomic consortia for high-throughput microscale screening of protein targets. , In addition to analyzing the structure and purity of molecules, NMR can also be used to determine the concentration of one or more chemical species in solution with a high precision and in a nondestructive manner. , Quantitative NMR (qNMR) has proven to be reliable, specific, and linear over a wide concentration range with limits of accuracy and precision in the order of 0.5–1%. The method is particularly suited for the simultaneous determination of the active constituents and impurities in samples from the food, pharmaceutical, and chemical industries. , Furthermore, a number of studies have used qNMR to specifically identify and quantify impurities in agrochemicals, pharmaceuticals, and amino acids and peptides; however, this is the first time to our knowledge that NMR has been used in the field of radiocarbon analysis.…”
mentioning
confidence: 99%
“…The latest generation of high-field NMR spectrometers equipped with microcryoprobes, however, extends the lower limits of detection of protonated species to the picomole scale. , The extreme sensitivity makes these probes ideal tools to study mass-limited samples such as isolated low-abundance proteins, peptides, and small molecules, and difficult to express proteins. For example, this technology has been used to determine the structures of molecules that can only be isolated in minute amounts (micrograms or less) from natural sources such as deep sea sponges, , red algae, and plants . It is also used by structural genomic consortia for high-throughput microscale screening of protein targets. , In addition to analyzing the structure and purity of molecules, NMR can also be used to determine the concentration of one or more chemical species in solution with a high precision and in a nondestructive manner. , Quantitative NMR (qNMR) has proven to be reliable, specific, and linear over a wide concentration range with limits of accuracy and precision in the order of 0.5–1%. The method is particularly suited for the simultaneous determination of the active constituents and impurities in samples from the food, pharmaceutical, and chemical industries. , Furthermore, a number of studies have used qNMR to specifically identify and quantify impurities in agrochemicals, pharmaceuticals, and amino acids and peptides; however, this is the first time to our knowledge that NMR has been used in the field of radiocarbon analysis.…”
mentioning
confidence: 99%
“…Shortolide C ( 1 ) and randainins C ( 2 ) and D ( 3 ) (Figure ) are structurally unique diterpenoids due to the simultaneous presence of the trans -hydroazulenone core and the C9-butenolide moiety. Bioassays showed that 1 is a moderate antibacterial agent against Staphylococcus aureus, whereas 3 inhibits elastase release and superoxide-anion generation.…”
Section: Introductionmentioning
confidence: 99%
“…Bicyclic diterpenoids, including clerodane, labdane, and halimane derivatives, are a large class of natural products found in several hundred plants, and they have attracted interest in recent years due to their notable bioactivities. Recently, some rearranged bicyclic diterpenoids have been reported as naturally occurring secondary metabolites, and these compounds include scopariusins A–C as examples of B- homo - ent -halimane derivatives with a 6/7-fused ring system, randainins A–D and shortolides B and C, which possess an A- homo -B- nor - or a B- homo -A- nor - ent -clerodane core with a 5/7- or 7/5-fused skeleton, and pentandranoic acids A and B, featuring a ring-A- nor - ent -clerodanoid with a 5/6-fused bicyclic framework. The widely distributed genus Callicarpa is known as a rich source of structurally diverse diterpenoids. ,, In this study, we reported seven new rearranged ent -clerodane diterpenoids (Figure ), callicarpins A–D ( 1 – 4 ), as the first examples with a unique 7/6-fused bicyclic system, callicarpins E–G ( 5 – 7 ), with a rare 5/6-fused ring skeleton, and a known diterpenoid ( 8 ) .…”
mentioning
confidence: 99%